Can changes in social contact (frequency and mode) mitigate low mood before and during the COVID‐19 pandemic? The I‐CONECT project. Issue 3 (13th December 2021) - Wu, Chao‐Yi; Mattek, Nora; Wild, Katherine; Miller, Lyndsey M.; Kaye, Jeffrey A.; Silbert, Lisa C.; Dodge, Hiroko H.
Abstract: Background/Objectives: The coronavirus disease 2019 (COVID‐19) global outbreak allowed a natural experiment to observe how older adults changed social patterns and how it affected their emotional well‐being. We studied the frequency and modes of social contact and their effects on older adults' mood before and during the COVID‐19 pandemic. Design: Phone‐based surveys were administered weekly before and during the COVID‐19 pandemic. Setting: Participants were recruited from Portland, Oregon, and Detroit, Michigan. Participants: Older adults ≥75 years old ( n  = 155, age = 81.0 ± 4.5, 72.3% women) were included in a randomized controlled trial, the Internet‐Based Conversational Engagement Clinical Trial (I‐CONECT). Measurements: Low mood was self‐reported as feeling downhearted or blue for three or more days in the past week. Social contact was self‐reported by the amount of time spent in interactions, with whom (family, friends, others), and via which modes (in‐person, phone/video call, text/email/letter). Results: A total of 5525 weeks of data were derived from 155 participants. Before the COVID‐19 pandemic, average social interaction time spent in‐person, on phone/video call, and via text/email/letter was 406, 141, and 68 min/week, respectively. During the COVID‐19 pandemic, time spent in‐person was reduced by 135 min/week, while time spent via phone/video call and writing increased by 33 and 26 mins/week, respectively. In‐person family contact was associated with less low mood regardless of the pandemic (odds ratio = 0.92, p  < 0.05). There was a COVID‐19 × text/email/letter with friends interaction (odds ratio = 0.77, p  = 0.03), suggesting that during the COVID‐19 pandemic, an increase of 1 h of writing with friends per week was associated with a 23% decrease in the likelihood of experiencing low mood. Conclusion: The lost in‐person time relating to COVID‐19 restrictions tended to be partially compensated for with increased calls and writing time, although overall social interaction time decreased. During the COVID‐19 pandemic, at least two types of social interactions (writing to friends and in‐person family time) showed promise for mitigating low mood for older adults with limited social resources.